Clinical consequence of mesiodens – A case series. Issue 3 (May 2016) - Mufeed, Abdulla; Hafiz, Abdul; Ashir, K.R.; Ahmed, Anis; Reshma, V.J.
Abstract: Mesiodens is the most common type of supernumerary tooth encountered in general dental practice. The clinical presentation may be varying depending on the position, number and relation to the adjacent tooth. Four cases of mesiodens with different patterns of presentation and clinical outcomes are presented here. Early detection by thorough clinical and radiographic evaluation allows adoption of less-complex and less-extensive treatment.